Anti-fascism in European History From the 1920s to Today - Pirjevec, Jože; Pelikan, Egon; Ramet, Sabrina (Central European University Press, 2023)
The increasing radicalization of political life in most countries in Europe lends special relevance to studies of the antifascist legacies on the continent. This insightful collection of essays is an in-depth review of antifascism in Slovenia, setting it in the context of related movements elsewhere in Europe. The period treated by the 19 essays comprises the interwar period, World War Two, and the post-war decades. The comparative and transnational perspectives advanced by the volume change our understanding of antifascism. The essays deal with the right-wing but also left-wing instrumentalization of antifascism, with a particular focus on the communist and post-communist periods. The authors point out that antifascism comes in various strains, whether inspired by liberalism, social democracy, communism, monarchism, anarchism, or even Christian conservatism. The contributors bring to light several overlooked antifascist actors, campaigns, and organisations, mostly in Slovenia and the Adriatic area.